A CONSTRUÇÃO DE MODELOS DIDÁTICOS NA IMPRESSORA 3D: UMA ABORDAGEM SIGNIFICATIVA PARA O ENSINO DE EMBRIOLOGIA - Roncaglio, Vanina (2020)
Embryology teaching is commonly memoristic and expository, with images in two dimensions, which leads students to have difficulties in overcoming epistemological obstacles in relation to embryology concepts. To arouse the interest of students, it is pertinent to use methodological alternatives that seek to remedy difficulties encountered by biology teachers in the teaching of embryology, with the 3D printer being a promising didactic tool to meet the needs that arise in the teaching-learning process. In this context, this work investigated the extent to which the use of this tool contributes to the significant critical learning of basic concepts of embryology, in Basic Education. For such a qualitative investigation, in an experimental design, a project was developed and applied with two first-year classes of high school in basic education. In class A the traditional methodology was used and in class B a didactic sequence was applied with the use and construction of embryonic 3D models. Data were collected through the researcher's private notes and pre and post-test questionnaires with both classes. The methodologies were compared using an attitudinal scale and content comprehension with levels from 1 to 6, with the first level for no concept and the last level for all concepts. Through the analysis of the results it was possible to observe the difference between the classes where class B was more naive, with a greater content deficit and less purchasing power in relation to class A. In this context it was observed that significant learning occurred, mainly in experimental class. The students demonstrated the overcoming of epistemological obstacles and constructed functional representations of the embryonic structures, deconstructing the inadequate previous concepts. Based on the result, it is possible to abstract that the use of educational technologies stimulates the student's interest, promoting significant critical learning in addition to making the students protagonists in the teaching-learning process.